Induction of Chloramphenicol Metabolism by Phenobarbital - Palmer, Darwin L. (1972)
The induction of hepatic microsomal enzymes leading to more rapid metabolism of antibiotics has been demonstrated in only a few prior studies. We have studied the induction of chloramphenicol metabolism in an isolated rat liver perfusion model and in intact dogs. Using these methods, we have demonstrated that the clearance of chloramphenicol from serum is markedly increased after treatment of animals with phenobarbital. This was demonstrated to be a function of increased clearance of the drug by the liver, accompanied but not paralleled by increases in liver weight and biliary excretion by the rat liver. In intact dogs, small doses of chloramphenicol were not sufficient to demonstrate this fact, whereas a large test dose of 100 mg/kg showed markedly enhanced clearance after 1 week of oral phenobarbital administration. Prolongation of phenobarbital treatment or increased dose did not further increase the clearance, and chloramphenicol could not be demonstrated to enhance its own clearance. Human data on induction of enzymes is to date inconclusive.